IBM Storage Networking SAN24B-6 Switch - Keenan, Ernest (IBM Redbooks, 2018)
This IBM® Redbooks® product guide describes the IBM Storage Networking SAN24B-6 switch. Explosive data growth, coupled with user expectations of unlimited access from anywhere, at any time, is pushing storage environments to the limit. To meet these dynamic business demands, the network must evolve to improve speed, increase efficiency, and reduce costs. Legacy infrastructures were not designed to support the performance requirements of flash-based storage technology. A new approach to storage networking is required to unlock the full capabilities of all-flash arrays. By treating the network as a strategic part of a storage environment, organizations can maximize their productivity and efficiency, even as they rapidly grow their environments. The IBM Storage Networking SAN24B-6 switch provides exceptional value in an entry-level switch, combining high-performance capabilities of 4, 8, 16, and 32 Gbps, point-and-click simplicity, and enterprise-class functionality. The port speed capability is dependent on the transceiver installed. SAN24B-6 provides small to midsized data centers with low-cost access to industry-leading Gen 5 and Gen 6 Fibre Channel technology and the ability to start small and grow on demand from 8 to 24 ports to support an evolving storage environment. In addition, SAN24B-6 is easy to use and install, with a point-and-click user interface that simplifies deployment and saves time.